Robust H-infinity control of a two-phase interleaved boost converter for second-life battery integration in battery energy storage systems - Alhosaini, Waleed; Aldosari, Obaid; Batiyah, Salem (Frontiers in Energy Research, 2025)
Integrating second-life batteries (SLBs) into energy storage systems (ESSs) offers a sustainable and cost-effective solution for extending battery utility. However, the inherent uncertainties and performance variations of these aged batteries present significant challenges in maintaining system stability and efficiency. Hence, this work introduces a robust control strategy employing an H-infinity H∞ controller to regulate a two-phase interleaved boost (IBC) converter interfacing SLBs. The IBC topology effectively steps up the output voltage of SLBs while reducing current ripple and enhancing overall system performance. Also, the developed H∞ control, combined with the IBC, ensures resilience against system uncertainties and load variations, which are common in applications involving SLBs. Extensive simulation results demonstrate that the proposed H∞ control achieves robust output voltage during transient and parameters uncertainties, when compared to classical PI controller. This validates the proposed system suitability for integrating SLBs into modern battery energy storage applications. The proposed H∞ controller demonstrated over 50% reduction in steady-state output ripples across various tested conditions, exhibited strong robustness under severe parameter mismatches, and achieved over 40% faster dynamic response compared to the conventional PI controller. These results validate the proposed system’s suitability for integrating SLBs into modern battery energy storage applications.